Parasitic diseases in African students: how international exchange programs could affect public health - Noya, Oscar; Elisa, María Campos; Losada, Sandra; Cárdenas, Jorge; Pabón, Rosalba; Contreras, Rosa; Colmenares, Cecilia; Alarcón de Noya, Belkisyolé; Valera, Alberto; Moreno, Sandra (Investigación Clínica, 2018)
Evidence shows that migratory processes alter the dynamics of infectious diseases, thus representing a challenge to public health in both a do- mestic and international scale. After the arrival of a group of 122 African medi- cal asymptomatic students to Venezuela for an educational exchange program, screening for eight parasitic diseases was done. The aim was to determine the presence of these diseases using standard parasitological tests, ELISA, immu- nochromatographic rapid test and MABA (Multiple Antigen Blot Assay). Six patients were found to have been carrying an active schistosomiasis and one was infected with Plasmodium falciparum. When using ELISA as the standard reference test, a total of 13 individuals were seropositive for toxoplasmosis, seven for amoebiasis, three for hydatidosis and two for cysticercosis. No pa- tients exhibited seropositivity for trypanosomiasis and fascioliasis according to ELISA. The introduction of infected individuals to the country might represent a threat to public health, which raises the need to establish screening protocols for asymptomatic people who intend to stay in Venezuela. In the frame of these results, recommendations regarding an appropriate evaluation for immigrants are discussed.